The Influence of Financial Literacy and Gender on Financial Behavior with Financial Technology as A Mediating Variable - Fauziyah, Nabil Nur; Sultan, Sultan; Dasila, Rifqa Ayu (PT. EQUATOR SINAR AKADEMIA, 2026)
This study analyzes the effect of financial literacy and gender on students’ financial behavior with financial technology as a mediating variable. A quantitative approach was employed through a survey of 96 students at Universitas Muhammadiyah Palopo who actively use fintech services. The data were analyzed using multiple linear regression. The results indicate that financial literacy and gender influence students’ financial behavior, and financial literacy also affects the use of financial technology. Financial technology acts as a mediating variable that strengthens the relationship between financial literacy and students’ financial behavior. Therefore, improving financial literacy and the wise use of financial technology are essential to promote healthier and more responsible financial behavior among students.